Impact of programming on primary mathematics learning. (December 2022) - Laurent, Manon; Crisci, Rosamaria; Bressoux, Pascal; Chaachoua, Hamid; Nurra, Cécile; de Vries, Erica; Tchounikine, Pierre
Abstract: The aim of this study is to investigate whether a programming activity might serve as a learning vehicle for mathematics acquisition in grades four and five. For this purpose, the effects of a programming activity, an essential component of computational thinking, were evaluated on learning outcomes of three mathematical notions: Euclidean division (N = 1, 880), additive decomposition (N = 1, 763) and fractions (N = 644). Classes were randomly assigned to the programming (with Scratch ) and control conditions. Multilevel analyses indicate negative effects (effect size range −0.16 to −0.21) of the programming condition for the three mathematical notions. A potential explanation of these results is the difficulties in the transfer of learning from programming to mathematics. Highlights: Compared to traditional activities, programming did not benefit mathematics learning. A negative though small effect of programming on mathematics learning was found. High-road transfer from programming to mathematics is not self-evident. Visual programming languages might distract students from mathematics activities.